Doenças infecciosas em crianças pré-escolares brasileiras assistidas em creches - Pedraza, Dixis Figueroa [UNESP]; Queiroz, Daiane de; Sales, Marcia Cristina [UNESP] (Associação Brasileira de Saúde Coletiva (ABRASCO), 2014)
The scope of this article is to analyze the prevalence and factors associated with the development of infectious diseases that affect children in daycare centers, namely respiratory infections, diarrheal disease and parasitic infections. Bibliographic research was conducted in the MEDLINE, LILACS and SciELO databases, and observational studies were included. 129 studies were identified, of which 21 were considered relevant to this study, namely two longitudinal and 19 cross-sectional studies. The systematization of the reviewed studies highlighted: i) the presence of intestinal parasites was the main outcome analyzed, followed by respiratory infections; ii) only one study investigated the occurrence of diarrheal disease; iii) the Giardia lamblia was the most prevalent parasitosis; iv) the variables that were most often associated with the development of intestinal parasitosis were child age, family income and maternal education; v) the attendance at daycare centers was a risk factor for intestinal parasites and respiratory infections. Respiratory and parasitic infections are major problems in institutionalized children in daycare centers. The reduction of such diseases involves a complex web of socio-economic, sanitation and daycare center infrastructure aspects.
Infectious diseases among Brazilian preschool children attending daycare centers
Keywords: Infection; Children; Daycare centers